Experience in Using 99mTc-Technephyt Esophageal Transit Scintigraphy for Assessing Pneumatic Dilation Outcome in Patients with Achalasia Cardia - R. A. Bashirov; A. I. Shelepova; L. E. Samoilenko; S. A. Ryzhkin; B. M. Sharafutdinov; A. F. Yusupova; L. F. Ziganshina; B. A. Magomedov; A. I. Kukushkin; V. Yu. Matveev; D. R. Bashirov (Вестник рентгенологии и радиологии, 2024)
Objective: to show the possibility of using 99mTc-technephyt esophageal transit scintigraphy (ETS) to assess the effect of cardiodilation in patients with achalasia cardia.Material and methods. We examined 7 patients (6 males and 1 female) aged 44–73 years (mean age 57.8 years) diagnosed with achalasia cardia, who were treated in Department of Thoracic Surgery No. 2 at Republican Clinical Hospital from June 2022 to January 2023. The disease duration before admission to the hospital ranged from 2 to 17 years (mean 9.2 years).Results. The analysis of ETS results showed a decreased radiopharmaceutical residual activity percentage in cardia for all patients after treatment compared with the initial data. It indicated a positive effect of cardiodilation and coincided with X-ray examination data. The obtained results demonstrate the possibility of ETS using and its practical significance to assess the effect of therapeutic measures, in particular cardiodilation, in patients with achalasia cardia.Conclusion. Performed according to the described protocol, ETS is a physiological and safe method for both the diagnosis of achalasia and the subsequent assessing therapeutic effect, including cardiodilation, myotomy, conservative treatment, and long-term dynamic monitoring. It is a physiological and safe procedure, which can be recommended in cases of difficulties in evaluating the esophageal function by X-ray, endoscopic and manometric methods or when their use is impossibile.